A ZIF-8-derived copper-nitrogen co-hybrid carbon catalyst for peroxymonosulfate activation to degrade BPA. (December 2022) - Sun, Yanping; Zhao, Yue; Zhan, Xiaohui; Gao, Rui; Chen, Lei; Yu, Jie; Wang, He; Shi, Huixiang
Abstract: A series of copper-nitrogen co-hybrid porous carbon catalysts were prepared by pyrolysis of copper-doped ZIF-8 in argon atmosphere. Both the precursors and the corresponding pyrolysis products retained the polyhedral morphology of ZIF-8. The catalytic performance of the catalysts obtained at different Cu doping levels and pyrolysis temperatures for PMS activation was compared by bisphenol A (BPA) degradation experiment. Among them 5%Cu-NC(8) catalyst obtained by pyrolysis of 5%Cu-ZIF-8 at 950 °C showed the best catalytic performance. The catalytic mechanism of PMS activation catalyzed by 5%Cu-NC(8) was analyzed by quenching experiment, ESR and XPS. The degradation pathways of BPA in 5%Cu-NC(8)/PMS system were proposed on the basis of LC-MS analyses. Pyridine N (including Cu–N), graphite N, CO group and the valence change of Cu were recognized as the catalytic active sites for 5%Cu-NC(8). Both free radical and non-free radical processes were involved in BPA degradation, and singlet oxygen ( 1 O2 ) was identified to be the main active substance. The stable performance and low Cu leaching rate in recycling experiment indicated that 5%Cu-NC(8) had good reusability and stability. This study provided a new insight for the design of heterogeneous copper-nitrogen co-hybrid carbon catalysts. Graphical abstract: Image 1 Highlights: 5%Cu-NC(8) catalysts were prepared by non-hydrothermal synthesis and pyrolysis. Pyridine N, graphite N, CO and the Cu-containing sites were the active sites. Both radical and non-radical processes were involved in PMS activation. 1 O2 was identified to be the main active substance in BPA degradation.